Knowledge systems and networks for nutrition in India: A review - Anuradha, T.N.; Kunaratnam, Yaso; McGrath, Louise (International Food Policy Research Institute, 2013)
The review provides an overview of the existing knowledge systems and networks (both physical and virtual) catering to nutrition-based information needs of policymaking audiences in India.